Old Norse Nicknames - Peterson, Paul, 1984- (2012)
Nicknames, which occur in all cultures and time periods, play a vital role in highlighting identity, and provide a window into popular culture. The function of nicknames in the Middle Ages is peculiar, however, when men (as in medieval Iceland) would kill for a carelessly dropped word if it was considered to be detrimental to their honor, yet often tolerated the most demeaning nicknames. The pool of personal names was limited, thus most people were identified with their nicknames. This circumstance created a trace in the interweaving saga plots where many nicknames recur across works. The quantity of nicknames in Old Norse literature is uniquely rich, and recurring nicknames provide a tool for understanding saga transmission and intertextuality. Saga nicknames may be ancient, formed earlier in the popular imagination, or fanciful interpretations penned by authors. They may have provided a basis for a character’s biography, and could be used to construct a narrative. Mentions of nicknames arise most often in the narratological circumstances in which they are appropriate, most often in the introduction of a chapter where new individuals and subsequent generations are illuminated. Most nicknames found in the sagas go unexplained, but dozens of passages comment on them. Where nicknames are explained, they most often appear in the narratological conditions of an anecdotal type. Nicknames are also important in providing motivation for actions or behavior (imagined by a saga author or otherwise) that occasionally plays a role in the plot. If a nickname was genuine (even if posthumous), many narratives developed from it and prove a degree of accuracy or inaccuracy in medieval memory and narrative transmission. Several categories of nicknames are found in Old Norse literature, such as those describing physical features, mental characteristics, or one’s deeds or habits (good or bad). Nicknames could be used in place of a given name in skaldic poetry, functioning similarly to heiti. Nicknames are also substituted for ...